Research on the Internal Flow Mechanisms and Pressure Fluctuation Characteristics of Seawater Reverse Osmosis Energy Recovery Turbines - Xiaobang Bai; Junhu Yang; Xueping Yuan; Xiaozhuang Chen; Bing Qi (Energies)
Energy recovery turbines (ERTs) play an important role in reducing the energy consumption of seawater reverse osmosis (SWRO). The internal flow loss mechanisms and hydraulic vibration characteristics of a centrifugal ERT model used in SWRO were studied under multiple conditions. The results show that the high-efficiency range of the ERT tends toward high-flow conditions. The energy loss is mainly concentrated at the tongue in the volute, which is due to the generation of flow separation vortices. There is a flow separation phenomenon on the suction surface side of the blade, trailing under the 0.8Qd condition. The energy loss of the ERT is the lowest under the 1.0Qd condition, because the interaction between the fluid and the blades is the weakest. There are vortices formed by flow impact on the blade pressure surface under the 1.2Qd condition. There are vortices on the blade suction face, which are generated by fluid separation. The closer the relative liquid flow angle is to the blade settle angle, the smaller the energy loss is in the impeller. Therefore, the ERT should first reduce rated flow appropriately before hydraulic design, as this is beneficial for efficient operation under multiple conditions.